Macroeconomic Effects of EU Enlargement for Old and New Members - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2001)
A new macroeconomic evaluation of EU enlargement is undertaken with a world macroeconomic model taking into account all possible integration effects: trade effects, Single Market effects, factor movements (FDI, migration) and the costs of enlargement. Due to the differences in size of the regions involved, on average the CEEC - measured in terms of real GDP - will gain around ten times more from enlargement than the EU. On average, enlargement is a win-win game. Hungary and Poland can increase their real GDP by around 8 to 9 percent over a ten year period, the Czech Republic gains a little bit less (5 to 6 percent). The EU on average would gain around percent of real GDP over a six year period. However, the impact is quite different in the separate EU member states, with Austria, Germany and Italy gaining the most and losses for Spain, Portugal and Denmark. Hence, EU enlargement acts like an exogenous shock leading to asymmetric disturbances in the EU. This could pause the process of business cycle synchronisation and might impair monetary policy in Euroland at the beginning of the enlargement process.
Keywords: F02; F15; C53; 330; EU enlargement; European integration; model simulations; EU-Mitgliedschaft; Europäische Integration; EU-Staaten; Ostmitteleuropa; Wirkungsanalyse